Vestibular evaluation with video head impulse test in pediatric cochlear implant patients - Teresa Pérez-Castillo; Silvia Ortiz-Rodríguez; Sandra K. Vélez-Pelcastre; Jessica Ma. González-Corona (Permanyer, 2024)
Background: The cochlear implant (CI) is effective for rehabilitating patients with severe to profound sensorineural hearing loss. However, its placement and use have been associated with various complications, such as those affecting the vestibular system. The objective of this study was to compare vestibular function using the video head impulse test (vHIT) in pediatric patients before and after CI placement. Methods: A descriptive and retrospective study was conducted. The outcomes of 11 pediatric patients of both sexes with a history of profound hearing loss were evaluated. The results of vestibular-ocular reflex (VOR) gain, saccades, asymmetry, Pérez Rey (PR) index, and VOR/saccade ratio for both ears obtained by the vHIT test before and after CI placement were compared. Results: Of the 11 patients evaluated, the VOR gain showed that 81.8% had normal function, 18.2% had hypofunction, and no patients had hyperfunction before implantation. No statistically significant differences were found when compared with post-implant off and post-implant on conditions (p > 0.05). The extracted variables, asymmetry, PR index, and the VOR/saccades ratio also showed no statistically significant differences between the pre- and post-implant conditions, whether off or on. Conclusions: The vestibular function of pediatric patients did not show significant changes before and after CI placement. The vHIT test is a valuable tool for assessing vestibular function and could be considered a criterion for surgical and rehabilitation decisions in patients undergoing CI placement.